Ischemic stroke : an atlas of investigation and treatment - Silverman, Isaac E. (Clinical Pub., 2009)
Over the past three decades, the diagnosis and treatment of stroke has changed at a phenomenal rate since the first use of CT scans and early studies using thrombolytic agents. New investigative procedures help direct patient selection for specific therapies and may substantially increase the chance of a successful therapeutic outcome. These advances in treatment have led to a paradigm shift in the way stroke victims are diagnosed and cared for. Specialists have seen the introduction of a range of new therapies for the management of ischemic stroke such as mechanical embolectomy and other cathe.